Do they know it's Christmastime at all?: Mad Men and the dangers of seasonal nostalgia. Issue 1 (1st April 2017) - Hoffman, Emily
Continuing an association between nostalgia and Christmas that originated after the reign of Queen Victoria in England, seasonal Christmas episodes on television have traditionally woven nostalgia and characters' journeys home into their plotlines. These plotlines seem to take a limited number of predictable forms that have remained remarkably consistent throughout television history. Regardless of the specific plot type, the episodes conclude with a heart-warming, optimistic ending that finds characters at home, happy and fulfilled. AMC's Mad Men (2007−2010), a show often considered to be emblematic of the so-called third golden age of US television, defies this tradition through its Thanksgiving and Christmas episodes that aggressively subvert viewer expectations. It often presents situations resembling those found in traditional seasonal episodes only to lead characters to moments of distress and discord rather than contentment and reconciliation. In these episodes, nostalgia has negative consequences, and is portrayed as the disease it was originally believed to be. Meanwhile, home is a site of danger, defilement, and destruction. It is not until Mad Men's final episode that characters are 'cured' of their nostalgia and the show delivers the type of uplifting ending that has been repeatedly deferred.